Seed Distribution Report for Kitui, Makueni, Taita Taveta and Baringo Counties - International Crops Research Institute for the Semi-Arid Tropics (International Livestock Research Institute, 2024)
Towards scaling up validated climate-smart technologies and addressing critical gaps in climate resilience and food security in Kenya’s drylands, the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project continues to enhance access to climate-smart innovations. A key focus of this effort is the dissemination of drought-tolerant and high-yielding seeds, crucial for improving food security among vulnerable smallholder farmers in these regions. On 31st August 2024, the Kenya Meteorological Department (KMD) issued a rainfall outlook for the October-November-December 2024 'Short Rains (OND 2024SR), predicting below-average rainfall for the Southern-eastern lowlands counties, including Kitui, Makueni and Taita Taveta. In response, and to strengthen farmers' preparedness for the OND 2024 season, the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), through the AICCRA project distributed drought-tolerant crop (DTC) seeds to beneficiary farmers in Kitui, Makueni and Taita Taveta Counties. The seed distribution exercise was carried out between 7th and 12th October 2024. Farmers received a variety of DTC seeds, including sorghum (Gadam and IESV 24029 SH), pigeon pea (ICEAP 01552, Mituki, Egerton Mbaazi 1, 3,4), pearl millet (KAT PM3) and green gram varieties (KS 20, Biashara, N26 and Karembo). The seed distribution was carried out in collaboration with county extension officers and Trainers of Trainers (ToTs). Earlier in September 2024, the ToTs registered new farmers as beneficiaries, particularly targeting those who had not previously received seeds through the AICCRA project. This ensured a wider reach of the drought-tolerant crops across the targeted wards. For the effectiveness of the seed distribution exercise, ToTs who conducted the registration process informed all registered farmers in advance to collect their seeds at designated points as planned.